The boy who flew - Hitchcock, Fleur (Nosy Crow, 2019)
Athan Wilde dreams of flight. When his friend, Mr Chen, is murdered, Athan must rescue the flying machine they were building together and stop it falling into the wrong hands. But keeping the machine safe puts his family in terrible danger. What will Athan choose - flight or family?
Keywords: Familie; Mord; Flugmaschine; Junge; Boys / Juvenile fiction; Families / Juvenile fiction; Murder / Juvenile fiction; Flying-machines / Juvenile fiction; Boys; Families; Flying-machines; Murder; Children's stories; Fiction; Juvenile works; Thrillers (Fiction); Kinderbuch